2019
DOI: 10.1177/0300060518816205
|View full text |Cite
|
Sign up to set email alerts
|

Fracture and dislocation of lumbar vertebrae with entrapment of small bowel: A case report and literature review

Abstract: Traumatic incarceration of the small bowel accompanied by vertebral fractures and dislocation is rare and usually misdiagnosed until laparotomy. This report presents a rare case of jejunum entrapment between lumbar spine fractures. A 43-year-old man was clamped between two railway tracks on the upper abdomen and lower back. Following ineffective conservative treatment, he underwent a laparotomy due to the development of guarding and rebound tenderness. Loss of vitality of the jejunal loop, which was incarcerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
(137 reference statements)
0
11
0
Order By: Relevance
“…[ 5 ] As in our case, traumatic vertebral fractures or dislocation-induced intestinal entrapment are extremely rare, and a study published in 2019 indicated that only 12 cases were reported from 1979 to 2016. [ 4 ] It is not a direct injury to the intestine due to instantaneous force from trauma, but rather a severe hyperextension injury of the spine, which is induced by torn anterior longitudinal ligament and herniation of the intestine. [ 6 , 7 ] This is due to obstruction and bowel strangulation caused by hernias may appear as symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 5 ] As in our case, traumatic vertebral fractures or dislocation-induced intestinal entrapment are extremely rare, and a study published in 2019 indicated that only 12 cases were reported from 1979 to 2016. [ 4 ] It is not a direct injury to the intestine due to instantaneous force from trauma, but rather a severe hyperextension injury of the spine, which is induced by torn anterior longitudinal ligament and herniation of the intestine. [ 6 , 7 ] This is due to obstruction and bowel strangulation caused by hernias may appear as symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 , 4 , 7 , 11 ] If bowel entrapment due to a fracture or dislocation of the spine is suspected, surgical treatment is necessary to manage the risk of complications or subsequent infection due to intestinal perforation. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations